The role of Israeli judges in authorising solitary confinement placements: Balancing human rights and risk, or neutralising responsibility?. (January 2023) - Dagan, Netanel; Shalev, Sharon
This paper explores the role of judges in authorising the extension of placements in solitary confinement in Israeli prisons for lengthy periods of time. It qualitatively examines, through content analysis of 354 Israeli court decisions, how judges negotiate and rationalise the harmful effects of solitary confinement when balanced against the prison authorities' reasoning for subjecting prisoners to it. Finding an overall tendency to defer to the expertise of prison authorities, we examine what Sykes & Matza termed 'techniques of neutralisation' used by judges to distance themselves from the responsibility for solitary confinement placements and the hardship they inflict. The paper further discusses the socio-legal and organisational structures and contexts which incentivise the prioritisation of prison security/discipline over the protection of prisoners from the 'pains of solitary confinement'.